High Resolution Seismic Inversion Using Combination Maximum-minimum (m-m) attribute and Zero-INTENS-Different (z-i-d) Attribute - Widi Purnomo, Eko (2010)
The good ability of Integrated-Energy-Spectra (INTENS) in resolving thin bed (thickness below tuning) structure has been joined with the minimum -maximum (m-m) or bandpass-filtered-peak-trough attribute of seismic for inverting below-tuning seismic. INTENS is defined as ratio or percentage of energy spectra in certain frequency against the energy spectra of the entire frequency of an seismic trace. INTENS consistently changes with every changes of reflection coefficient separation. The low resolution inverted thickness of m-m attribute is used as initial earth-reflectivity model. The model then convolved with an extracted-wavelet to provide synthetic seismic. The INTENS of true seismic and it's synthetic are calculated and then subtracted to get INTENS-different. The INTENS-different calculation is repeated every separation of coefficient-reflection is shifted to construct INTENS-different profile. The resolution of the model then enhanced by analyzing the profile of INTENS-difference between the true seismic and it's synthetic. In the condition of free-noise seismic and perfect wavelet, the true layer thickness (coefficient reflection separation) is pointed by zero INTENS-different. Further analysis is needed to obtain the true thickness when the seismic is noisy and the wavelet is imperfect. The corrected coefficient-reflection separation then transformed to impedance map which has more beneficiaries for reservoir characterization. The method has been implemented to invert the seismic of Stratton field which rich of subtle structure. The method provides 3D-map of pseudo-impedance of Stratton's shallow sand- channel very well.